Improving Reading Culture Through Reading Corner Activities at SDN 004 Sungai Piring - Asyrul Fikri Irul; Monalisa Putri Lisa; Ririn Oktavia Irin (International Journal of Public Devotion, 2022)
Community Service Program (KUKERTA) after the pandemic is a very different activity from previous KUKERTA activities. Having KUKERTA after this pandemic has really helped local residents and the school. The purpose of this service is to increase public understanding and concern for children's education. The KUKERTA Team for Sungai Piring Sub-district carried out one of the work programs in one of the schools located in the Sungai Piring Sub-District, namely the 004 Sungai Petani Public Elementary School. The results of this service illustrate the increasing enthusiasm for learning and interest in reading in students. Reading is important in the teaching and learning process. Each student has varying reading abilities and reading interests. Adequate support, habituation and facilities will increase students' interest in reading at SDN 004 Kelurahan Sungai Rompin. The objects of the research are teachers and all students at SDN 004 Kelurahan Sungai Piring